Preparation method of modified basalt fiber and polyimide composite material
By constructing a polydopamine adhesion layer on the surface of basalt fibers and grafting nanosilica and graphene oxide to form a multi-scale roughened interface structure, the problem of low bond strength in basalt fibers and polyimide composites is solved, and the mechanical properties and wear resistance of the composite are improved.
Patent Information
- Application Number
- CN202510652521.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-21
- Publication Date
- 2025-08-05
AI Technical Summary
The bonding strength between the fiber and the matrix in basalt fiber and polyimide composite materials is low, resulting in insufficient mechanical properties and wear resistance.
Through the oxidative autopolymerization reaction of dopamine in weakly alkaline solution, a polydopamine adhesion layer is constructed on the surface of basalt fibers, and then nanosilicon dioxide and graphene oxide are grafted to form a multi-scale roughened interface structure. The modified basalt fiber/thermoplastic polyimide composite material is prepared by thermal molding method.
The interface bonding strength between basalt fiber and thermoplastic polyimide composite material is improved, the stress distribution is uniform, and the mechanical properties and wear resistance of the composite material are improved.
Smart Images

Figure CN120424503A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and in particular to a method for preparing a modified basalt fiber and polyimide composite material. Background Art
[0002] Fiber-reinforced resin composites are widely used in heat-resistant, wear-resistant, and load-bearing components in the automotive, aerospace, and other fields due to their lightweight, high specific strength, strong impact resistance, and short molding cycles. Polyimide (PI), a polymer material with excellent overall performance, possesses a unique imide ring structure that imparts exceptional high-temperature resistance, good mechanical strength, and corrosion resistance, with a long-term operating temperature range of -200°C to 300°C. However, pure PI resin still suffers from insufficient mechanical properties and poor tribological stability under complex operating conditions, hindering its further application.
[0003] Basalt fiber (BF), one of the four high-performance fibers being developed in my country, boasts a chemical composition primarily composed of oxides such as 45-60% SiO2, 12-18% Al2O3, and 8-15% FeO. It offers advantages such as lightweight, high strength, corrosion resistance, and high and low-temperature resistance. Compared to traditional glass fiber, BF exhibits superior corrosion resistance and environmental friendliness while maintaining similar mechanical properties and production costs. However, due to limitations such as its high surface chemical inertness and weak fiber-matrix interface, BF is unable to fully realize its potential for strengthening and toughening.
[0004] Hot compression molding is an important method for preparing resin-based composite materials due to its strong process controllability, low internal stress in the product, and stable mechanical properties. This process, which is performed at temperatures below the melting point of the matrix, effectively maintains the properties of the material components and is particularly suitable for preparing multi-component composite materials with high strength, toughness, and wear resistance. However, PI resins have the characteristics of high melt viscosity and a narrow molding window. In addition, the low thermal conductivity of BF can easily lead to uneven matrix curing, making the molding of complex-component PI-based friction materials challenging. Therefore, systematically studying the effects of parameters such as molding temperature, pressure, and holding time on interface structure and friction properties is of great significance for the development of high-performance PI-based brake materials.
[0005] To address these issues, the present invention proposes a process for the synergistic modification of BF using dopamine / nanosilica / graphene oxide. Through the oxidative self-polymerization of dopamine in a weakly alkaline solution, a polydopamine (PDA) adhesion layer is constructed on the BF surface. Nanosilica (SiO2 NPs) and graphene oxide (GO) are then grafted onto the surface, forming a multi-scale roughened interface structure. After hot-pressing the modified BF and PI resin, the composite material exhibits enhanced interfacial bonding strength and reduced wear rate. This modification process is characterized by its simplicity and environmental friendliness, and has great potential for application. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a preparation method of modified basalt fiber and polyimide composite materials in response to the above-mentioned deficiencies in the existing technology, solve the problem of low bonding strength between basalt fiber and matrix in basalt fiber / thermoplastic polyimide composite materials, and prepare resin-based composite materials with good mechanical properties and wear resistance, and provide a controllable molding method of dopamine-synergistically modified basalt fiber / thermoplastic polyimide composite materials.
[0007] The present invention provides a method for preparing a modified basalt fiber and polyimide composite material, comprising the following steps:
[0008] S1. Surface modification of basalt fiber:
[0009] S101, polydopamine-modified basalt fiber: prepare a Tris-HCl buffer solution, add basalt fiber and dopamine hydrochloride, and then ultrasonically disperse. After stirring in a water bath at room temperature, wash and dry to obtain polydopamine-modified basalt fiber;
[0010] S102, amination of nano-silica: adding KH550 to a mixture of anhydrous ethanol and deionized water to prepare a mixed solution, stirring at room temperature, adding nano-silica, and stirring in a water bath to prepare an amination nano-silica aqueous solution;
[0011] S103, amination of graphene oxide: dissolving graphene oxide in an anhydrous ethanol solution, performing a primary ultrasonic dispersion to prepare a graphene oxide solution, adding KH550 to a mixture of anhydrous ethanol and deionized water to prepare a mixed solution, then mixing the mixed solution with the graphene oxide solution, performing a secondary ultrasonic dispersion, and stirring in a water bath to obtain an amination graphene oxide solution;
[0012] S104, aminated nano-silica grafted basalt fiber: take the aminated nano-silica aqueous solution obtained in S102, add it to the polydopamine-modified basalt fiber obtained in S101, ultrasonically disperse it, stir it in a water bath, wash it, and dry it to obtain nano-silica grafted basalt fiber;
[0013] S105. Nano-silica synergistically grafted onto basalt fibers: The aminated graphene oxide aqueous solution obtained in S103 was added to the nano-silica grafted basalt fibers obtained in S104, and the mixture was ultrasonically dispersed and stirred in a water bath. The mixture was washed and dried to obtain nano-silica synergistically grafted onto graphene oxide GO-SiO2NPs-PBF basalt fibers.
[0014] S2, hot pressing:
[0015] S201, taking polyimide powder and the GO-SiO2NPs-PBF obtained in S1, stirring and mixing to obtain a mixture, placing the mixture into a molding die for cold pressing, and then hot compression molding on a high-temperature mechanical press vulcanizer. After the heat and pressure holding is completed, cooling to room temperature and demolding to obtain a sample;
[0016] S202. The sample is dried and then cooled to room temperature to obtain GO-SiO2NPs-PBF / PI.
[0017] According to the preparation method of the modified basalt fiber and polyimide composite material provided by the present invention, the pH value of the Tris-HCL buffer solution in S101 is 7.5-10.5, the concentration of the Tris-HCL buffer solution is 0.5-2 g / L, the amount of basalt fiber added to the Tris-HCL buffer solution is 1-40 g / L, the amount of dopamine hydrochloride added is 1-5 g / L, the ultrasonic dispersion time is 20-30 min, the stirring time is 24-36 h, the drying temperature is 120-130° C., and the drying time is 6-8 h.
[0018] According to the preparation method of the modified basalt fiber and polyimide composite material provided by the present invention, the volume ratio of anhydrous ethanol and deionized water in the mixed solution in S102 is 2:1, the KH550 content in the mixed solution is 1-6%, the amount of nano-silica added is 0.2-1g, the stirring time is 20-30min, the temperature of the water bath stirring is 52-58°C, and the water bath stirring time is 1-1.5h.
[0019] According to the preparation method of the modified basalt fiber and polyimide composite material provided by the present invention, in S103, the concentration of the graphene oxide solution in S103 is 1-10 g / L, the time of the first ultrasonic dispersion is 20-30 min, the volume ratio of anhydrous ethanol and deionized water in the mixed solution is 2:1, the content of KH550 in the mixed solution is 1-6%, the time of the second ultrasonic dispersion is 10-20 min, the temperature of the water bath stirring is 65-78° C., and the time of the water bath stirring is 2-3 h.
[0020] According to the preparation method of the modified basalt fiber and polyimide composite material provided by the present invention, the mass volume ratio of the amino-modified nano-silica aqueous solution and the polydopamine-modified basalt fiber in S104 is 1:20, the ultrasonic dispersion time is 10 to 20 minutes, the water bath stirring temperature is 50 to 60°C, the water bath stirring time is 1 to 2 hours, the drying temperature is 100 to 110°C, and the drying time is 4 to 6 hours.
[0021] According to the preparation method of the modified basalt fiber and polyimide composite material provided by the present invention, the mass volume ratio of the amino-treated graphene oxide aqueous solution and the nano-silica grafted basalt fiber in S105 is 1:10, the ultrasonic dispersion time is 20 to 30 minutes, the water bath stirring temperature is 76 to 86°C, the water bath stirring time is 2 to 2.5 hours, the drying temperature is 120°C, and the drying time is 8 to 12 hours.
[0022] According to the preparation method of the modified basalt fiber and polyimide composite material provided by the present invention, the stirring time in S201 is 20 minutes, the mass ratio of polyimide powder to GO-SiO2NPs-PBF in the mixture is 15-16:3-4, the pressure of the cold pressing is 5 MPa, the holding time is 5 minutes, and the procedure of the hot molding is: heating from room temperature to 200°C at a heating rate of 10°C / min, keeping warm and holding pressure at a pressure of 15-20 MPa for 10 minutes, during which the pressure is released and exhausted 4-5 times; then heating to 260-270°C and keeping warm and holding pressure for 20 minutes, during which the pressure is released and exhausted 2-3 times; finally heating to 320-340°C and keeping warm and holding pressure for 50-60 minutes.
[0023] According to the method for preparing a modified basalt fiber and polyimide composite material provided by the present invention, the drying temperature in S202 is 180-240° C., and the drying time is 1-4 hours.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] The present invention provides a method for preparing a modified basalt fiber and polyimide composite material. Through the oxidative autopolymerization reaction of dopamine in a weakly alkaline solution, a polydopamine adhesion layer is constructed on the basalt fiber surface. Nano-silica and graphene oxide are then grafted onto the surface to form a multi-scale roughened interface structure. A modified basalt fiber / thermoplastic polyimide composite sample was prepared using a hot molding method. The modification of the basalt fiber surface with nano-silica and graphene oxide effectively improves its surface activity, enabling it to form a good interfacial bond with the thermoplastic polyimide resin matrix. This homogenizes stress distribution and inhibits interfacial debonding of the composite material, thereby enhancing the mechanical properties and wear resistance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the present invention or the prior art, a brief introduction will be given below to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0027] Figure 1 This is the SEM morphology of the untreated basalt fiber (BF) in Comparative Example 1.
[0028] Figure 2 This is the SEM morphology of polydopamine-modified basalt fiber (PBF) in Comparative Example 2.
[0029] Figure 3 This is the SEM morphology of nano-silica grafted polydopamine modified basalt fiber (SiO2NPs-PBF) in Comparative Example 3.
[0030] Figure 4 This is the SEM morphology of basalt fiber modified with polydopamine (GO-SiO2NPs-PBF) synergistically grafted with nano-silica and graphene oxide in Example 1.
[0031] Figure 5 Vickers hardness of the composite materials obtained by hot molding process for Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1;
[0032] Figure 6 The compressive strength of the composite materials obtained by the hot molding process in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1;
[0033] Figure 7 The flexural strength of the composite materials obtained by the hot molding process in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1;
[0034] Figure 8 The average friction coefficient of the composite materials prepared by the hot molding process of Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1;
[0035] Figure 9 The wear rates of the composite materials prepared by the hot molding process in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 are shown. DETAILED DESCRIPTION
[0036] An embodiment of the present invention provides a method for preparing a modified basalt fiber and polyimide composite material, comprising the following steps:
[0037] S1. Surface modification of basalt fiber:
[0038] S101. Polydopamine-modified basalt fiber: prepare a Tris-HCl buffer solution with a concentration of 0.5-2 g / L and a pH of 7.5-10.5, add basalt fiber and dopamine hydrochloride, wherein the amount of basalt fiber added to the Tris-HCl buffer solution is 1-40 g / L and the amount of dopamine hydrochloride added is 1-5 g / L, and then ultrasonically disperse for 20-30 minutes. After stirring in a water bath at room temperature for 24-36 hours, wash with deionized water three times, and dry at 120-130° C. for 6-8 hours to obtain polydopamine-modified basalt fiber (PBF), which is set aside.
[0039] S102, amination of nano-silica: adding KH550 to a mixture of anhydrous ethanol and deionized water in a volume ratio of 2:1 to prepare a mixed solution with a KH550 content of 1-6%, stirring at room temperature for 20-30 minutes, then adding 0.2-1 g of nano-silica, and stirring in a water bath at 52-58° C. for 1-1.5 hours to prepare an amination nano-silica aqueous solution;
[0040] S103, amination of graphene oxide: dissolving graphene oxide in an anhydrous ethanol solution, performing a primary ultrasonic dispersion for 20 to 30 minutes to obtain a graphene oxide solution having a concentration of 1 to 10 g / L, adding KH550 to a mixture of anhydrous ethanol and deionized water in a volume ratio of 2:1 to obtain a mixed solution having a KH550 content of 1 to 6%, then mixing the KH550 mixed solution with the graphene oxide solution, performing a secondary ultrasonic dispersion for 10 to 20 minutes, and stirring in a water bath at 65 to 78° C. for 2 to 3 hours to obtain an amination graphene oxide solution;
[0041] S104, aminated nano-silica grafted basalt fiber: take 0.5-1 L of the aminated nano-silica aqueous solution obtained in S102, add 10-20 g of the polydopamine-modified basalt fiber obtained in S101, ultrasonically disperse for 10-20 min, stir in a water bath at 50-60° C. for 1-2 h, wash four times with deionized water, and dry at 100-110° C. for 4-6 h to obtain nano-silica grafted basalt fiber;
[0042] S105. Nano-silica synergistically grafted onto basalt fiber with graphene oxide: 0.5-1 L of the amino-treated graphene oxide aqueous solution obtained in S103 was added to 5-10 g of the nano-silica grafted basalt fiber obtained in S104, and the mixture was ultrasonically dispersed for 20-30 min, stirred in a water bath at 76-86° C. for 2-2.5 h, washed twice with deionized water, and dried at 120° C. for 8-12 h to obtain nano-silica synergistically grafted onto graphene oxide GO-SiO2NPs-PBF, abbreviated as BF;
[0043] S2, hot pressing:
[0044] S201, using a mechanical blending process to uniformly disperse polyimide (PI) powder and GO-SiO2NPs-PBF obtained in S1 in a planetary ball mill for 20 minutes, the mass ratio of PI to BF in the mixture is 15-16:3-4; the mixture is placed in a molding mold for cold pressing, the pressure is set to 5MPa, and the holding time is; then hot molding is performed on a high-temperature mechanical press vulcanizer: heating from room temperature to 200℃ at a heating rate of 10℃ / min, keeping the temperature at 15-20MPa for 10 minutes, during which the pressure is released and exhausted 4-5 times; then heating to 260-270℃, keeping the temperature at 20 minutes, during which the pressure is released and exhausted 2-3 times; finally heating to 320-340℃, keeping the temperature at 50-60 minutes, cooling to room temperature and demolding after the end of the holding period;
[0045] S202. Place the sample in a forced air drying oven at 180-240°C for 1-4 hours. Cool the oven to room temperature and take out the sample to obtain GO-SiO2NPs-PBF / PI.
[0046] Example 1
[0047] This embodiment provides a method for preparing a modified basalt fiber and polyimide composite material, and the specific steps are as follows:
[0048] S1. Surface modification of basalt fiber:
[0049] S101. Polydopamine-modified basalt fiber: Prepare 0.7 L of Tris-HCl buffer solution with a concentration of 1 g / L and a pH value of 8.5, add 10 g of basalt fiber and 1.2 g of dopamine hydrochloride, and then ultrasonically disperse for 20 min. Stir in a water bath at room temperature for 24 h. Then, wash three times with deionized water and dry at 120°C for 6 h to obtain polydopamine-modified basalt fiber (PBF) for later use.
[0050] S102, amination of nano-silica: KH550 (γ-aminopropyltriethoxysilane) was added to a mixture of anhydrous ethanol and deionized water in a volume ratio of 2:1 to prepare a mixed solution with a KH550 content of 2%, and the mixture was stirred at room temperature for 20 minutes. Then, 0.2 g of nano-silica was added, and the mixture was stirred in a water bath at 52° C. for 1 hour to prepare an amination nano-silica aqueous solution;
[0051] S103, amination of graphene oxide: dissolving 1 g of graphene oxide in 1 L of anhydrous ethanol solution, ultrasonically dispersing for 20 min to prepare a graphene oxide solution, adding KH550 to a mixture of anhydrous ethanol and deionized water in a volume ratio of 2:1 to prepare a mixed solution with a KH550 content of 2%, then mixing the KH550 mixed solution with the graphene oxide solution, ultrasonically dispersing for 10 min, and stirring in a water bath at 65° C. for 2 h to obtain an amination graphene oxide solution;
[0052] S104, aminated nano-silica grafted basalt fiber: 0.5 L of the aminated nano-silica aqueous solution obtained in S102 was added to 10 g of the polydopamine-modified basalt fiber obtained in S101, and ultrasonically dispersed for 10 min. The mixture was stirred in a water bath at 50°C for 1 h. After washing four times with deionized water, the mixture was dried at 100°C for 4 h to obtain nano-silica grafted basalt fiber.
[0053] S105. Nano-silica synergistically grafted onto basalt fiber with graphene oxide: 0.5 L of the amino-treated graphene oxide aqueous solution obtained in S103 was added to 5 g of the nano-silica grafted basalt fiber obtained in S104, and the mixture was ultrasonically dispersed for 30 min. The mixture was stirred in a water bath at 76°C for 2 h, washed twice with deionized water, and dried at 120°C for 8 h to obtain nano-silica synergistically grafted onto graphene oxide GO-SiO2NPs-PBF, abbreviated as BF.
[0054] S2, hot pressing:
[0055] S201. Polyimide (PI) powder and GO-SiO2NPs-PBF obtained in S1 were uniformly dispersed in a planetary ball mill for 20 minutes using a mechanical blending process. The mass ratio of PI to BF in the mixture was 16:3. The mixture was placed in a molding mold for cold pressing, with the pressure set to 5MPa and the holding time being 5min. Then, hot compression molding was performed on a high-temperature mechanical press vulcanizer: the mold was heated from room temperature to 200°C at a heating rate of 10°C / min, and kept at this temperature and pressure for 10min at 15MPa, during which the pressure was released and exhausted 5 times. Then the temperature was raised to 260°C and kept at this temperature and pressure for 20min, during which the pressure was released and exhausted 3 times. Finally, the temperature was raised to 320°C and kept at this temperature and pressure for 60min. After the heat preservation and pressure holding period, the mold was cooled to room temperature and demolded.
[0056] S202. Place the sample in a 200°C forced air drying oven and keep it warm for 2 hours. After the oven cools to room temperature, take out the sample to obtain GO-SiO2NPs-PBF / PI.
[0057] Example 2
[0058] This embodiment provides a method for preparing a modified basalt fiber and polyimide composite material, and the specific steps are as follows:
[0059] S1. Surface modification of basalt fiber:
[0060] S101. Polydopamine-modified basalt fiber: Prepare 1 L of Tris-HCl buffer solution with a concentration of 1.5 g / L and a pH of 9.5, add 20 g of basalt fiber and 2.4 g of dopamine hydrochloride, and then ultrasonically disperse for 30 min. Stir in a water bath at room temperature for 36 h. Then, wash with deionized water four times and dry at 130°C for 8 h to obtain polydopamine-modified basalt fiber for later use.
[0061] S102, amination of nano-silica: KH550 was added to a mixture of anhydrous ethanol and deionized water in a volume ratio of 2:1 to prepare a mixed solution with a KH550 content of 4%, and the mixture was stirred at room temperature for 30 minutes. Then, 1 g of nano-silica was added, and the mixture was stirred in a water bath at 58° C. for 1.5 hours to prepare an amination nano-silica aqueous solution;
[0062] S103, amination of graphene oxide: dissolving 2 g of graphene oxide in 2 L of anhydrous ethanol solution, ultrasonically dispersing for 30 min to prepare a graphene oxide solution, adding KH550 to a mixture of anhydrous ethanol and deionized water in a volume ratio of 2:1 to prepare a mixed solution with a KH550 content of 4%, then mixing the KH550 mixed solution with the graphene oxide solution, ultrasonically dispersing for 20 min, and stirring in a water bath at 78°C for 3 h to obtain an amination graphene oxide solution;
[0063] S104, aminated nano-silica grafted basalt fiber: 1 L of the aminated nano-silica aqueous solution obtained in S102 was added to 20 g of the polydopamine-modified basalt fiber obtained in S101, and the mixture was ultrasonically dispersed for 20 min. The mixture was stirred in a water bath at 60°C for 2 h, washed four times with deionized water, and dried at 110°C for 6 h to obtain nano-silica grafted basalt fiber.
[0064] S105. Nano-silica synergistically grafted onto basalt fiber with graphene oxide: 1 L of the amino-treated graphene oxide aqueous solution obtained in S103 was added to 10 g of the nano-silica grafted basalt fiber obtained in S104, and the mixture was ultrasonically dispersed for 20 min. The mixture was stirred in a water bath at 86°C for 2.5 h, washed three times with deionized water, and dried at 120°C for 12 h to obtain nano-silica synergistically grafted onto graphene oxide GO-SiO2NPs-PBF, abbreviated as BF.
[0065] S2, hot pressing:
[0066] S201. Polyimide (PI) powder and GO-SiO2NPs-PBF obtained in S1 were uniformly dispersed in a planetary ball mill for 20 minutes using a mechanical blending process. The mass ratio of PI to BF in the mixture was 15:4. The mixture was placed in a molding mold for cold pressing, with the pressure set to 5MPa and the holding time being 5min. Then, hot molding was performed on a high-temperature mechanical press vulcanizer: the mold was heated from room temperature to 200°C at a heating rate of 10°C / min, and kept at this temperature and pressure for 10min at 20MPa, during which the pressure was released and exhausted 4 times. Then the temperature was raised to 270°C and kept at this temperature and pressure for 20min, during which the pressure was released and exhausted 2 times. Finally, the temperature was raised to 340°C and kept at this temperature and pressure for 50min. After the heat preservation and pressure holding period, the mold was cooled to room temperature and demolded.
[0067] S202. Place the sample in a 240°C forced air drying oven and keep it warm for 3 hours. After the oven cools to room temperature, take out the sample to obtain GO-SiO2NPs-PBF / PI.
[0068] Comparative Example 1
[0069] Compared with Example 1, this comparative example 1 omitted the surface modification treatment of basalt fiber in S1, and other method steps were the same;
[0070] The sample made of unmodified basalt fiber and thermoplastic polyimide was recorded as BF / PI.
[0071] Comparative Example 2
[0072] Compared with Example 1, this comparative example 2 omitted the basalt fiber surface modification treatments S102, S103, S104 and S105 in S1, and other method steps were the same;
[0073] The sample made of polydopamine-modified basalt fiber and thermoplastic polyimide was recorded as PBF / PI.
[0074] Comparative Example 3
[0075] Compared with Example 1, this comparative example 3 omitted the basalt fiber surface modification treatments S103 and S105 in S1, and other method steps were the same;
[0076] The sample prepared by nano-silica grafted polydopamine modified basalt fiber and thermoplastic polyimide was recorded as SiO2NPs-BF / PI.
[0077] Example 3
[0078] The products prepared in Example 1 and Comparative Examples 1 to 3 were characterized.
[0079] ① Figure 1This is the SEM morphology of the unmodified basalt fiber (BF) in Comparative Example 1. As can be seen from the figure, the surface of the unmodified basalt fiber is smooth without obvious grooves or protrusions.
[0080] ② Figure 2 This is the SEM morphology of the polydopamine-modified basalt fiber (PBF) in Comparative Example 2. It can be seen from the figure that polydopamine is attached to the surface of the basalt fiber.
[0081] ③ Figure 3 This is the SEM morphology of the nano-silica grafted polydopamine modified basalt fiber (SiO2NPs-PBF) in Comparative Example 3. It can be seen from the figure that the nano-silica is relatively evenly distributed on the surface of the basalt fiber.
[0082] ④ Figure 4 The SEM morphology of nano-silica and graphene oxide synergistically grafted polydopamine modified basalt fiber (GO-SiO2NPs-PBF) in Example 1;
[0083] As can be seen from the figure, obvious flake graphene oxide and nano-silica are deposited on the surface of basalt fibers with good dispersion, forming a multi-scale surface roughness structure.
[0084] ⑤ Figure 5 、 Figure 6 and Figure 7 The Vickers hardness, compressive strength and flexural strength performance diagrams of the composite material samples prepared by the hot molding process in Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 are shown.
[0085] As can be seen from the figure, the Vickers hardness, compressive strength and flexural strength of the composites of polydopamine-modified basalt fiber (PBF), silica-grafted polydopamine-modified basalt fiber (SiO2NPs-PBF), graphene oxide synergistically with silica-grafted polydopamine-modified basalt fiber (GO-SiO2NPs-PBF) and thermoplastic polyimide are significantly improved, and the effect of GO-SiO2NPs-PBF is better.
[0086] The Vickers hardness, compressive strength and flexural strength of the GO-SiO2NPs-PBF / PI composite material are 71.05HV, 286.32MPa and 170.56MPa, respectively, which are 25.04%, 30.05% and 30.99% higher than those of the BF / PI composite material prepared in Comparative Example 1.
[0087] This is attributed to the introduction of polydopamine, nano-silica, and graphene oxide onto the basalt fiber surface. The adhesion of polydopamine allows the nano-silica and graphene oxide to adhere more tightly to the basalt fiber surface, increasing the roughness of the basalt fiber surface while also introducing chemical bonds between the basalt fiber and the polyimide matrix. This creates a reinforced structure of mechanical interlocking and chemical bonding at the fiber-matrix interface, effectively improving the interfacial strength between the fiber and resin.
[0088] ⑥ Figure 8 、 Figure 9 The friction coefficient curves and wear rate diagrams of the composite material samples prepared by the hot molding process for Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 after grinding against GCr15 for 60 minutes under a load of 9N.
[0089] Figure 8 Among them, the average friction coefficient of BF / PI is 0.66, the average friction coefficient of SiO2NPs-PBF / PI is 0.588, the average friction coefficient of GO-SiO2NPs-PBF / PI is 0.568, and the average friction coefficient of PBF / PI is 0.631.
[0090] It can be seen from the figure that the average friction coefficient and wear rate of PBF / PI, SiO2NPs-PBF / PI and GO-SiO2NPs-PBF / PI composites are lower than those of BF / PI, and the average friction coefficient and wear rate of GO-SiO2NPs-PBF / PI are the lowest.
[0091] Among them, the average friction coefficient and wear rate of GO-SiO2NPs-PBF / PI were the lowest, 0.568 and 0.537×10 -5 mm 3 / (N·m), which were reduced by 13.94% and 38.63% compared with BF / PI, respectively.
[0092] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent variation made to the above embodiment based on the essence of the invention technology shall still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing a modified basalt fiber and polyimide composite material, characterized in that: The following steps are involved: S1. Surface modification of basalt fiber: S101, polydopamine-modified basalt fiber: prepare a Tris-HCl buffer solution, add basalt fiber and dopamine hydrochloride, and then ultrasonically disperse. After stirring in a water bath at room temperature, wash and dry to obtain polydopamine-modified basalt fiber; S102, amination of nano-silica: adding KH550 to a mixture of anhydrous ethanol and deionized water to prepare a mixed solution, stirring at room temperature, adding nano-silica, and stirring in a water bath to prepare an amination nano-silica aqueous solution; S103, amination of graphene oxide: dissolving graphene oxide in an anhydrous ethanol solution, performing a primary ultrasonic dispersion to prepare a graphene oxide solution, adding KH550 to a mixture of anhydrous ethanol and deionized water to prepare a mixed solution, then mixing the mixed solution with the graphene oxide solution, performing a secondary ultrasonic dispersion, and stirring in a water bath to obtain an amination graphene oxide solution; S104, aminated nano-silica grafted basalt fiber: take the aminated nano-silica aqueous solution obtained in S102, add it to the polydopamine-modified basalt fiber obtained in S101, ultrasonically disperse it, stir it in a water bath, wash it, and dry it to obtain nano-silica grafted basalt fiber; S105. Nano-silica synergistically grafted onto basalt fibers: The aminated graphene oxide aqueous solution obtained in S103 was added to the nano-silica grafted basalt fibers obtained in S104, and the mixture was ultrasonically dispersed and stirred in a water bath. The mixture was washed and dried to obtain nano-silica synergistically grafted onto graphene oxide GO-SiO2NPs-PBF basalt fibers. S2, hot pressing: S201, taking polyimide powder and the GO-SiO2NPs-PBF obtained in S1, stirring and mixing to obtain a mixture, placing the mixture into a molding die for cold pressing, and then hot compression molding on a high-temperature mechanical press vulcanizer. After the heat and pressure holding is completed, cooling to room temperature and demolding to obtain a sample; S202. After drying, the sample is cooled to room temperature to obtain GO-SiO2NPs-PBF / PI.
2. The method for preparing the modified basalt fiber and polyimide composite material according to claim 1, characterized in that: The pH value of the Tris-HCL buffer solution in S101 is 7.5-10.5, the concentration of the Tris-HCL buffer solution is 0.5-2 g / L, the amount of basalt fiber added to the Tris-HCL buffer solution is 1-40 g / L, the amount of dopamine hydrochloride added is 1-5 g / L, the ultrasonic dispersion time is 20-30 min, the stirring time is 24-36 h, the drying temperature is 120-130° C., and the drying time is 6-8 h.
3. The method for preparing the modified basalt fiber and polyimide composite material according to claim 1, characterized in that: The volume ratio of anhydrous ethanol and deionized water in the mixed solution in S102 is 2:1, the content of KH550 in the mixed solution is 1-6%, the amount of nano-silica added is 0.2-1 g, the stirring time is 20-30 min, the temperature of the water bath stirring is 52-58° C., and the stirring time in the water bath is 1-1.5 h.
4. The method for preparing the modified basalt fiber and polyimide composite material according to claim 1, characterized in that: The concentration of the graphene oxide solution in S103 is 1 to 10 g / L, the time for the first ultrasonic dispersion is 20 to 30 min, the volume ratio of anhydrous ethanol to deionized water in the mixed solution is 2:1, the KH550 content in the mixed solution is 1 to 6%, the time for the second ultrasonic dispersion is 10 to 20 min, the temperature for water bath stirring is 65 to 78° C., and the time for water bath stirring is 2 to 3 h.
5. The method for preparing the modified basalt fiber and polyimide composite material according to claim 1, characterized in that: The mass volume ratio of the amino-containing nano-silica aqueous solution and the polydopamine-modified basalt fiber in S104 is 1:20, the ultrasonic dispersion time is 10 to 20 minutes, the water bath stirring temperature is 50 to 60°C, the water bath stirring time is 1 to 2 hours, the drying temperature is 100 to 110°C, and the drying time is 4 to 6 hours.
6. The method for preparing the modified basalt fiber and polyimide composite material according to claim 1, characterized in that: The mass-to-volume ratio of the amino-treated graphene oxide aqueous solution and the nano-silica-grafted basalt fiber in S105 is 1:10, the ultrasonic dispersion time is 20 to 30 minutes, the water bath stirring temperature is 76 to 86° C., the water bath stirring time is 2 to 2.5 hours, the drying temperature is 120° C., and the drying time is 8 to 12 hours.
7. The method for preparing the modified basalt fiber and polyimide composite material according to claim 1, characterized in that: The stirring time in S201 is 20 minutes, the mass ratio of polyimide powder to GO-SiO2NPs-PBF in the mixture is 15-16:3-4, the pressure of the cold pressing is 5 MPa, the holding time is 5 minutes, and the procedure of the hot compression molding is: heating from room temperature to 200°C at a heating rate of 10°C / min, keeping warm and holding pressure at a pressure of 15-20 MPa for 10 minutes, during which the pressure is released and exhausted 4-5 times; then heating to 260-270°C and keeping warm and holding pressure for 20 minutes, during which the pressure is released and exhausted 2-3 times; finally heating to 320-340°C and keeping warm and holding pressure for 50-60 minutes.
8. The method for preparing the modified basalt fiber and polyimide composite material according to claim 1, characterized in that: The drying temperature in S202 is 180-240° C., and the drying time is 1-4 hours.